Knowledge, attitude and belief about organ donation of people in the area of Prasat, Kap-Choeng and Phanom-Dong-Rak District, Surin Province. - Thobpae, Prueksachat (Journal of Human and Society, Sisaket Rajabhat University, 2022)
This research focused on knowledge, attitude, and belief about organ donation of people in the area of Prasat, Kap-Choeng, and Phanom-Dong-Rak district, Surin Province. The sample group consisted of 436 community leaders in Prasat District. The participants were divided into a group by purposive sampling includes people in 3 districts area by in-depth and focus group interviews during ten times of active campaign and collecting data during May 2018 - May 2019. The research instruments are a questionnaire developed by the researcher, a semi-and structured interview, data analysis using descriptive statistics, and content analysis techniques. The study found that 1) all participants were Buddhism or 238 people, more than half are the chief of the village, they had expressed their intention to donate organs or eye donation only 8 cases of 238 cases or 1.8 percent. There were 268 participants as 61.2 percent who received the information from the medical staff on organ donation. 2) Knowledge concerning organ donation is the most accurate answer as 234 persons, representing 53.7 percent on the issue of organ donation as the healthy condition organs can use to transplant in the recipient 3) the sample group had a moderate level of attitudes and beliefs on all issues related to significant informant group who had participated in an active campaign, informant group were Buddhism principles.